Roman pottery and glass manufactures : production and trade in the Adriatic region and beyond : proceedings of the 4th International Archaeological Colloquium (Crikvenica, 8-9 November 2017) - Lipovac Vrkljan, Goranka,; Konestra, Ana,; Borzić, Anamarija Eterović, (Archaeopress Roman archaeology ;, 2022)
This edited volume presents 31 papers read at the 4th International Archaeological Colloquium held in Crikvenica, Croatia, 8-9 November 2017. The papers deal with issues of pottery production in relation to landscape and communication features, ceramic building materials, as well as general studies on ceramic production, pottery and glass finds. Additionally, an invited contribution explores finds relating to clothing from the Roman pottery workshop at Crikvenica. Several papers are devoted to restoration and archaeological experimentation. Although the majority of papers tackle research conducted in the wider Adriatic area, several contributions deal with other provinces of the Roman world.